An Analysis of Protection System the Quality of Blood Warmer Device Based on Over Temperature Sensor - Vivi Wilyanti; Solly Aryza; Hamdani, Hamdani (Sean Institute, 2024)
A blood warmer is a medical device used to warm blood before transfusion to prevent hypothermia in patients. One of the main challenges in using this device is maintaining the blood temperature within a safe range, preventing blood quality degradation and potential harm to the patient. To address this issue, an effective protection system is required, one of which involves an over-temperature sensor. This study analysed the implementation of a protection system based on an over-temperature sensor in blood warmer devices to ensure both blood quality and patient safety. The method used in this research involves the design and testing of a protection system with temperature sensors that can detect over-temperature conditions in real-time. If the temperature exceeds the specified limit, the system automatically shuts off the heating process to prevent damage to the blood. Data obtained from testing show that the developed protection system operates accurately with a fast response time. The test results also demonstrate that the blood quality is maintained within a safe temperature range during the transfusion process. Thus, the over-temperature sensor-based protection system implemented in the blood warmer device can enhance the device's safety and reliability, ensuring that the quality of blood transfused to patients remains intact. This study is expected to serve as a reference in the development of safer and more effective medical devices.